Методичні рекомендації щодо рейтингування економічних показників підприємств - Григор’єв, О. Ю.; Тодощук, А. В.; Габор, Я. Я.; Hryhoriev, O. Yu.; Todoshchuk, A. V.; Habor, Ya. Ya. (Видавництво Львівської політехніки, 2023)
У статті досліджено основні проблеми вітчизняної нормативно-методичної бази для рейтингування юридичних осіб за економічними показниками в умовах європейської інтеграції. Запропоновано методичні рекомендації з визначення економічного рейтингу юридичної особи на основі кредиту соціальної довіри, аналог якого застосовується у Китайській Народній Республіці та на основі досвіду провідних країн світу. Рекомендації можуть бути застосовані державними органами України з метою мінімізації корупції в країні, а також прозорості надання пільг, привілеїв, субсидій, дотацій.

The introduction of the economic rating will contribute to the centralization of control over the activities of economic entities by various state bodies. On the other hand, the economic rating will allow to avoid subjectivity in the evaluation of the economic activity of enterprises by state bodies and other subjects of economic activity and to establish a transparent and understandable work of the state bodies themselves for subjects of economic activity and society as a whole. It consists in a careful study and analysis of the international and domestic experience of rating the economic activity of enterprises according to economic and economic indicators in Ukraine in order to develop agreed and unified methodological recommendations for the ranking of business entities in the process of European integration of Ukraine. To determine the rating of the company by economic indicators, it is necessary to evaluate the main indicators of the economic activity of the enterprise, minimizing and simplifying their calculation, and to introduce a digital rating of the economic indicators of the company. With two-way communication between the enterprise and other market participants, this will simplify relations between them. On the other hand, state bodies will be able to direct the development of enterprises in the right direction, according to the adopted policy of socio-economic development. The proposed recommendations will help to simplify the conditions for obtaining privileges by honest and conscientious enterprises in the form of quotas, licenses, permits, benefits, subsidies. The proposed system will enable government bodies, as well as other commercial institutions, to conduct a kind of audit of the enterprise, to see the overall picture of the state of its activity, to transparently select the best in the industry and grant them privileges. In addition, the rating will help reduce the number of inspections of the enterprise by government authorities, which are often inefficient and ineffective.
Methodological recommendations for digital rating of economic indicators of enterprises
Keywords: рейтинг; критерій; показник; рейтингова шкала; економічне рейтингування; rating; criterion; indicator; rating scale; economic rating; 338.2; 336; 658